2006
DOI: 10.1029/2004jd005694
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation mode aerosol, pockets of open cells, and particle nucleation in the remote subtropical Pacific marine boundary layer

Abstract: [1] We analyze a marine boundary layer cloud field encountered during the second research flight of the second Dynamics and Chemistry of Marine Stratocumulus Experiment. The cloud field is distinguished by the presence of pockets of open cells. Differences between the pockets and the surrounding stratocumulus clouds are studied utilizing in situ and satellite data. The pockets are characterized as regions where cloud radar echo tops are unusually variable, accumulation mode aerosol concentrations are low, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
92
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(106 citation statements)
references
References 50 publications
14
92
0
Order By: Relevance
“…The open-cell structures are called Pockets of Open Cells (POCs) or rifts (Sharon et al, 2006). Their origin is not fully understood, but significant differences in aerosol and cloud microphysical properties between POCs and the surrounding clouds are typically observed Petters et al, 2006;Sharon et al, 2006;Wood et al, 2008Wood et al, , 2011a. VanZanten and Stevens (2005), Sharon et al (2006), and Wood et al (2011a) found that POCs are characterized by enhanced drizzle, although drizzle itself seem insufficient for transition from closed-to open-cell circulations Wood et al (2011a).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…The open-cell structures are called Pockets of Open Cells (POCs) or rifts (Sharon et al, 2006). Their origin is not fully understood, but significant differences in aerosol and cloud microphysical properties between POCs and the surrounding clouds are typically observed Petters et al, 2006;Sharon et al, 2006;Wood et al, 2008Wood et al, , 2011a. VanZanten and Stevens (2005), Sharon et al (2006), and Wood et al (2011a) found that POCs are characterized by enhanced drizzle, although drizzle itself seem insufficient for transition from closed-to open-cell circulations Wood et al (2011a).…”
Section: Published By Copernicus Publications On Behalf Of the Europementioning
confidence: 99%
“…We estimate the random error on the cloud forcing is less than ±10 Wm −2 , which is due to measurement, interpolation and radiation transfer calculation errors. Cloud radar reflectivity was obtained using a Kband millimeter wavelength cloud radar (Moran et al, 1998). CCN were measured with two identical in situ CCN counters (Roberts and Nenes, 2005).…”
Section: Observations and Model Descriptionmentioning
confidence: 99%
“…Bretherton et al, 2004;Comstock et al, 2005;Stevens et al, 2005;Petters et al, 2006;Wood et al, 2008Wood et al, , 2011a; and references therein). Very briefly, local dynamical processes leading to enhanced drizzle formation in Sc clouds remove moisture and cloud condensation nuclei (CCN) from the boundary layer, thus suppressing recovery of the cloud from the moisture sink of drizzle.…”
Section: Introductionmentioning
confidence: 99%